Plantations, privatization, poverty and power : changing ownership and management of state forests - Garforth, Michael; Mayers, James (London ; Sterling, VA : Earthscan, 2005)
"Examines the evidence and explores the many issues raised by changing relationships between the state, the private sector and local livelihoods. Key lessons in how governments can best achieve a balance between private and public involvement are provided by seven case studies from Australia, China, Chile, India, New Zealand, South Africa and the United Kingdom"--Provided by publisher
Chapter 11: From Plantation Developer to Steward of the Nation's ForestsNotes; References; Index.
Includes bibliographical references (pages 272-288) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Forest reserves -- Management; Tree farms -- Management; Private forests -- Management; Réserves forestières -- Gestion; Forêts privées -- Gestion; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; Forest reserves -- Management; Tree farms -- Management; Forstwirtschaft; Plantagenwirtschaft; Privatisierung; Staatsforst; Vermögenspolitik; Waldbesitzer; Electronic books; Aufsatzsammlung